Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B; Colombaroli, D; Chapron, E; Leroux, A; Tinner, W; Magny, M (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B.; Colombaroli, D.; Chapron, E.; Leroux, A.; Tinner, W.; Magny, M. (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M. Blanca Ruiz; Jos, M.; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M Blanca Ruiz; Jos, M; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Une flore d'âge ougartien (seconde partie du quaternaire moyen) dans les monts d'ougarta (Sahara Nordoccidental) - Beucher, Françoise (Review of Palaeobotany and Palynology, 1967)
The analysis of a series of samples carried out in the versicoloured conglomerates of the “Oued Farès” (Ougarta Mountains, western Sahara) gives the first conception of what the vegetation was like in this region throughout the Ougartian (second phase of the Middle Quaternary). Superimposing on the herbaceous layer which widely represents the desert-like xerophyte element, the arborescent flora bears the imprint of diverse influences: a typical Mediterranean influence (Quercus ilex, Quercus coccifera, Pinus halepensis, Cedrus cf. atlantica, Oleaceae, Anacardiaceae, Vitis, Argania); an influence undoubtedly of the mountainous zones of the eastern Mediterranean (Alnus, Ulmus, Carpinus betulus, Salicaceae), and finally a tropical influence (Acacia, cf. Sapindaceae). If one should attempt to characterize the three main episodes which the stratigraphy permits one to distinguish in these formations studied on the spot (Lower Ougartian, Middle Ougartian, Upper Ougartian), one can recognize from the Lower Ougartian a relatively dry period both preceded and followed by a more humid phase; during the Middle Ougartian the climatic conditions favourize the simultaneous blooming of Mediterranean species and those of the outer Sahel; the Upper Ougartians remains poorly characterized by a very limited number of pollen grains.
Keywords: Climatic conditions; Middle Quartenary; Ougarta Mountains; vegetation history (PG)